Youth, violence and health: the construction of information in processes of knowledge mediation and appropriation - DOI: 10.3395/reciis.v3i3.275en - Regina Maria Marteleto (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
This is a report of a study on how youngsters from lower economical classes in large cities, as information subjects,transform the established meanings of discursive and narrative forms - the "third knowledge" -, revealing the influence of physical and symbolic violence suffered from state, media, school, and society, that results on negative representation for their identities. The subjects include youngsters from projects conducted by non-governmental organizations, by the state or social movements. We use the concepts of mediation and social knowledge appropriation to study how they translate their violence experiences into their symbolic reserve. We present an informational experiment, a fanzine,regarding urban violence and its effects on young people, that was carried out in the research process. The interpretative analysis based on qualitative methodology indicates a symbolic and identity conflict in a possible informational action taken on the violent contexts where these youngsters live.